Uji Efek Nefroprotektif Ekstrak Kulit Buah Mangga Arumanis (Mangifera indica L) Secara In Vivo Diinduksi Gentamisin - Ifmaily Ifmaily; Irwandi Irwandi; Essi Fadila Warni (Journal of Pharmaceutical and Health Research, 2023)
Mango rind is one of the organic wastes after we eat the fruit. In previous studies, mango rind extract has been shown to have antihypertensive, antidiabetic, and antioxidant effects from its secondary metabolite flavonoids. The purpose of this study was to determine the effect of mango rind extract (EKBM) as a nephroprotector in male rats, and to determine the effect of varying doses of EKBM as a nephroprotector in male rats using creatinin level, ureum level, and weight ratio of rats’kidney. This study was purely experimental, using 25 white male rats with 5 groups of rats consisting of 5 rats per groups. The group was a negative control group, positive control, doses of 100 mg/kgbw, 150 mg/kgbw, 200 mg/kgbw, except for the negative control, all of which were induced with gentamicin for 5 days. On the 9th day, blood was taken through the orbital vein, then centrifuged, the serum was taken to check the creatinine level, then the rats were killed and weighed by the weight ratio of the rat kidneys. The results of this study were negative control, positive control, doses of 100 mg/kgbw, 150 mg/kgbw, and 200 mg/kgbw for creatinine levels in rats 0.74; 2.7; 0.76; 1,37; 1.4 (mg/dl), ureum levels; 28,7; 125,8; 28,9; 35,8; 43,5 ( mg/dl ) and for animal kidney weight 1,97 ; 2,74 ; 2,13 ; 2,15 ; dan 2,19 (%). The conclusion is that mango rind extract can provide a nephroprotector effect and the mango rind extract can provide a nephroprotector effect with an effective dose of 100 mg/kgbb with a p value = 0.047